Synthesis and characterization of zeolites from palm oil fuel ash (POFA) by ultrasonic assisted hydrothermal approach - Syafiqah Amira, Khairuddin (2018)
Palm oil fuel ash (POFA), is a type of waste from palm oil mill. Its components are almost similar as those of fly ash and agro-wastes such as rice husk ash, and sugarcane bagasse ash, which is, silica and alumina. The presence of both compounds has led to the synthesis of zeolite, which is a highly useful material. Abundance of POFA in palm oil mill, lack of its application and lead to serious environmental problem became concern to minimize POFA. This research concentrated on the investigation of the synthesis of zeolites from POFA by using ultrasonic assisted hydrothermal method. The present study was conducted in various conditions using several KOH: POFA ratios (1:1- 5:1), ultrasound water bath temperatures (40-80 °C), ultrasound exposure times (30-150 minutes), ultrasound power levels (400-800 W) and KOH concentration levels (1-5 M). Commonly, hydrothermal and fusion techniques have been widely used in the production of zeolite. However, these techniques would require high energy consumption, making them less economical and time-consuming because zeolite production may take several days. The effect of the five parameters were investigated on the synthesized zeolites in order to achieve best conditions for pollution-free and environmenal friendly synthesis during and after the experimental process. Characterization of raw POFA and synthesized zeolites were determined by X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), BET surface area, Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). This was followed by the optimisation study of zeolites in combination with half factorial design and central composite design. Results showed that the optimum conditions for zeolite synthesis from POFA were KOH: POFA ratio of 2:1, ultrasonic water bath temperature at 80 °C, ultrasonic exposure time of 150 minutes and KOH concentration level at 1 M which eventually produced zeolites with high silica per alumina ratio (10.60) that fulfilled zeolite standard range of silica per alumina (2-10). Based on the optimum conditions, XRD results indicated the phases of zeolite synthesized matched those of zeolites A, P and X. FTIR spectra detected the presence of functional groups that were common for zeolites. Silica per alumina ratio for the optimum conditions which is 10.60, indicated the hydrophobic adsorbent property of the synthesized zeolite. As shown by SEM, the surface was comparable to that of zeolites A, P and X. It has been evident from past studies that zeolite A, P and X have been commonly used as adsorbent. Thus, it can be said that the present study has successfully achieved the optimum synthesis condition that would be able to produce high silica per alumina zeolite with adsorbent property. To improve the quality of zeolites, separation of crude zeolites as well as development of other methods and process parameters should be given consideration.